Dithia[9]helicenes: Molecular design, surface imaging, and circularly polarized luminescence with enhanced dissymmetry factors. Issue 38 (13th September 2022) - Baciu, Bianca C.; Bronk, Pawel J.; de Ara, Tamara; Rodriguez, Rafael; Morgante, Pierpaolo; Vanthuyne, Nicolas; Sabater, Carlos; Untiedt, Carlos; Autschbach, Jochen; Crassous, Jeanne; Guijarro, Albert
Abstract : Synthesis of two dithia[9]helicenes by means of a LED-based double photocyclization is reported. Abstract : Synthesis of two dithia[9]helicenes by means of a LED-based double photocyclization is reported. The compounds have sulfur atoms placed at the terminal rings of the helicene, and they display two alternative C 2 -symmetrical arrangements named exo (1 ) and endo (2 ). Separation of enantiomers of opposite helicity allowed the complete characterization in solution, in silico, by X-ray crystallography, and adsorbed on gold. The theoretical analysis confirms the unexpected finding that endo -dithia[9]helicene displays an experimental dissymmetry factor ( g lum ) in CPL larger than its isomer exo -dithia[9]helicene (–0.0125 vs. −0.0042). This enhanced g lum factor ranks among the largest for a helicene-type molecule. Comparison with smaller analogues, namely exo and endo -dithia[7]helicenes (10 and 11, respectively), is also presented.